Inculcating IKS cultural practices into the pre-service science and mathematics teacher education curriculum at an Institution of Higher Education in Namibia - Ngololo, Elizabeth Ndeukumwa; Kasanda, Choshi Darius (ARKA INSTITUTE, 2024)
In this paper we interrogate the teachers training programme offered at an institution of higher learning in Namibia. We used Empiricism to explore the authentic practices used in the transformational processes exposed to 3rd and 4th year mathematics and science student teachers. We emphasized three important constructs that guide the scholarship of teaching, namely standards of excellence, virtues and values to guide IK integration in the curriculum. We conclude that student teachers understood the meaning and importance of IK. However, the teacher preparation curriculum did not include aspects related to IK, it was left at their own discretion to adopt. We recommend appropriate strategies for adoption to implement and guide the required standards and values for curriculum development.